Speckle noise reduction in high speed polarization sensitive spectral domain optical coherence tomography - Götzinger, Erich (Opt Express, 2011)
We present a high speed polarization sensitive spectral domain optical coherence tomography system based on polarization maintaining fibers and two high speed CMOS line scan cameras capable of retinal imaging with up to 128 k A-lines/s. This high imaging speed strongly reduces motion artifacts and therefore averaging of several B-scans is possible, which strongly reduces speckle noise and improves image quality. We present several methods for averaging retardation and optic axis orientation, the best one providing a 5 fold noise reduction. Furthermore, a novel scheme of calculating images of degree of polarization uniformity is presented. We quantitatively compare the noise reduction depending on the number of averaged frames and discuss the limits of frame numbers that can usefully be averaged.